Institutional capacities in the transfer of the Judicial Facilitators Program - Castillo, Daniela (Journal Studies of Public Policy, 2019)
The article is framed in the policy transfer approach to study the role of institutional capacities in the configuration of the decision-making process, taking as a case study the Paraguayan adoption of the Nicaraguan model of Judicial Facilitators, as public access policy to justice promoted by the Organization of American States in the region. Through the application of the process tracing method, the process by which Paraguay obtained and used the model information for the design of public policy was tracked. The main finding of the investigation refers to the emulation of the model of judicial facilitators, product of the low institutional capacities, which were reflected in the inability of its technical teams to generate new evidence, limiting the design of public policy to the information presented and validated by the country in which the idea was developed and by the promoter of the model.